Penetration twins of olivine in alkaline melanocratic basalts from the collection of N.M. Przhevalsky - E. V. Putintseva; E. M. Spiridonov (Известия высших учебных заведений: Геология и разведка, 2015)
The extremely rare penetration twins of olivine for (031) and (011) in alkaline melanocratic basalts of East Mongolia from the collection of the famous scientist-traveller N.M. Przhevalsky, which is stored in the museum of the department of petrography of St. Petersburg state university. The possible reasons for the appearance of growth twins of olivine are examined. The